2011
DOI: 10.1016/j.jaci.2011.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rituximab on human in vivo antibody immune responses

Abstract: Background B-lymphocyte depletion with rituximab has been shown to benefit patients with various autoimmune diseases. We have previously demonstrated that this benefit is also apparent in patients with newly diagnosed type 1 diabetes. Objectives The effect of rituximab on in vivo antibody responses, particularly during the period of B-lymphocyte depletion, is incompletely determined. This study was designed to assess this knowledge void. Methods In patients with recent-onset type 1 diabetes treated with ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 33 publications
6
72
0
Order By: Relevance
“…The examinations performed on healthy volunteers and on patients with bacterial infections indicated that bacteriophages may have an influence on induction of antiphage antibody production (9,11). A safety test of PT performed by Bruttin and Brüssow (3) on 15 adult healthy volunteers using E. coli T4 phage orally indicated no increase in level of antiphage IgG, IgM, and IgA in the serum after 1 month of the study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The examinations performed on healthy volunteers and on patients with bacterial infections indicated that bacteriophages may have an influence on induction of antiphage antibody production (9,11). A safety test of PT performed by Bruttin and Brüssow (3) on 15 adult healthy volunteers using E. coli T4 phage orally indicated no increase in level of antiphage IgG, IgM, and IgA in the serum after 1 month of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Kamme (8) also examined the level of antiphage antibodies in sera of 100 healthy volunteers, which showed a low level of antiphage antibodies for S. aureus phages mostly up to serum dilution 1:80. Pescovitz et al (11) performed a study of 52 healthy volunteers who received the E. coli uX174 phage intravenously. E. coli uX174 phage was in the body for 3-4 days after administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results underscore the need for further studies on the role of B lymphocytes in maintaining the chronic islet autoimmunity. In mice, it has been demonstrated that there is a significant crossspresentation of autoantigens to CD8+ T cells that precipitates diabetes (ref 47 . The observations on autoantibody and neoantigen responses is underscoring the importance of the B cell as an antigen-presenting cell that may not only interact with T helper cells but also directly with other antigen presenting cells such as dendritic cells to induce autoantibody formation ( Figure 6).…”
Section: Rituximab -An Cd20 Monoclonal Antibodymentioning
confidence: 99%
“…Consequently, protection against meningococcal disease by antibody-mediated killing becomes essential. However, vaccination of patients using immunosuppressive drugs may be ineffective (3,4). Different immunosuppressive regimens vary in their effects on humoral responses after vaccination.…”
Section: To the Editormentioning
confidence: 99%